Gender Equality Expression as a Biological Homeostasis Principle Applied in Social Mechanisms of Child-Friendly Schools - Saliman (Postgraduate, University of Mataram, 2024)
This research explores the application of gender equality principles within Child-Friendly Schools (CFS), specifically at Harapan Mandiri High School in Medan, through the lens of biological homeostasis principles applied to social mechanisms. Utilizing a descriptive qualitative approach, this study draws on primary data collected from guidance counseling teachers at the school, using observation and in-depth interviews as data collection techniques. The findings reveal that Harapan Mandiri High School effectively implements gender equality by ensuring equal access, opportunities, treatment, and participation for both male and female students. The fairness in treatment is evident in assessments, rewards, and discipline, while student engagement is fostered through participation in student organizations and extracurricular activities. The school’s focus on preventing discrimination and promoting gender awareness contributes to a safe and inclusive learning environment, enhancing respect for gender diversity. This successful implementation of gender equality principles reflects the school’s commitment to creating a balanced and inclusive educational environment, akin to maintaining homeostasis in biological systems, where equilibrium is achieved through equitable participation and treatment of all students.